2018
DOI: 10.1007/s00784-018-2614-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter evaluation of immediately functionalized tapered conical connection implants for single restorations in maxillary anterior and premolar sites: 3-year results

Abstract: The presented treatment is a viable option for single-tooth restorations of maxillary anterior teeth and premolars with successful short- to mid-long-term clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 40 publications
2
26
0
3
Order By: Relevance
“…A statistically significant improvement in PES from the baseline score (definitive crown fit stage) to the 1-year review was noted in both the groups (den Hartog et al 2 , Gjelvold et al 35 ). Heydecke et al 37 and Raes et al 38 reported an improvement from baseline in the immediately loaded cohort at 1-year review, and PES stabilised for the next two years; these studies did not report conventional loading. Den Hartog et al 2 reported an improvement in the mean PES from 1-year review to 5-year review in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A statistically significant improvement in PES from the baseline score (definitive crown fit stage) to the 1-year review was noted in both the groups (den Hartog et al 2 , Gjelvold et al 35 ). Heydecke et al 37 and Raes et al 38 reported an improvement from baseline in the immediately loaded cohort at 1-year review, and PES stabilised for the next two years; these studies did not report conventional loading. Den Hartog et al 2 reported an improvement in the mean PES from 1-year review to 5-year review in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…All the RCT’s that compared immediate loading with conventional loading identified no clinically significant statistical difference in the PES at 1 year (den Hartog et al 2 , Gjelvold et al 35 ) and at 5 years (den Hartog et al 2 ). Cohort studies reported comparable PES for the immediately loaded implants to the contralateral tooth (Heydecke et al 37 Raes et al 38 ). All studies except one study (Hall et al 36 ) reported PES as an aesthetic outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random effects model Allen et al, 2017Bashutski et al, 2013Cooper et al, 2001Cooper et al, 2007Cooper et al, 2014Esposito et al, 2015Friberg et al, 2019Grandi et al, 2013Heydecke et al, 2019Hosseini et al, 2019Hsu et al, 2016(a) Jonker et al, 2018Kemppainen et al, 1997Meijndert et al, 2019Norton, 2004Palmer et al, 2000Raes et al, 2015Vanlioglu et al, 2012Vanlioglu et al, 2014Wittneben et al, 2020Yildiz et al, 2016…”
Section: Studymentioning
confidence: 99%
“…Random effects model Allen et al, 2017Bashutski et al, 2013Cooper et al, 2001Cooper et al, 2007Cooper et al, 2014Esposito et al, 2015Friberg et al, 2019Grandi et al, 2013Heydecke et al, 2019Hosseini et al, 2019Hsu et al, 2016(a) Jonker et al, 2018Kemppainen et al, 1997Meijndert et al, 2019Norton, 2004Palmer et al, 2000Raes et al, 2015Vanlioglu et al, 2012Vanlioglu et al, 2014Wittneben et al, 2020Yildiz et al, 2016 Canullo et al, 2013Canullo et al, 2017 Hartog et al, 2016Den Hartog et al, 2017Felice et al, 2015Fu et al, 2014Gjelvold et al, 2017Gjelvold et al, 2020Guarnieri et al, 2016Hsu et al, 2016 Cooper et al, 2001Cooper et al, 2007Cooper et al, 2014Hosseini et al, 2019Raes et al, 2015…”
Section: Studymentioning
confidence: 99%